Proton-Transfer Mediated Quenching of Pyrene/Indole Charge-Transfer States in Isooctane Solutions - Altamirano, Marcela Susana (2008)
The fluorescence quenching of pyrene (Py) by a series of N-methyl and N-H substituted indoles was studied in isooctane at 298 K. The fluorescence quenching rate constants were evaluated by mean of steady-state and time-resolved measurements. In all cases, the quenching process involves a charge-transfer (CT) mechanism.The Io/I and to/t Stern-Volmer plots obtained for the N-H indoles show a very unusual upward deviation with increasing concentration of the quenchers. This behavior is attributed to the self-quenching of the CT intermediates by the free indoles in solution. The efficiency of quenching of the polyaromatic by the N-H indoles increases abruptly in the presence of small amount of added pyridine (or propanol). A detailed analysis of the experimental data obtained in the presence of pyridine provides unambiguous evidence that the selfquenching process involves proton transfer from the CT states to indoles.